Klauzule rozłączności w konwencjach Rady Europy - Paweł Filipek (Ksiegarnia Akademicka Publishing, 2014)
Under the auspices of the Council of Europe more than 200 international agreements were drafted and concluded. They foster closer cooperation primarily among member states and set Pan‑European legal standards. In some Council of Europe conventions special clauses have been introduced that allow a group of parties for a derogation from convention obligations – they are known as “disconnection clauses”. Disconnection clauses resemble conflict of law rules, are general in nature, normally are formulated in a unconditional way, and operate automatically. They are meant to provide protection for regulations established by more closely integrated states, e.g. Nordic states or the European Union. For the latter, they are crucial as they safeguard the EU autonomy and uphold primacy of EU rules vis‑à‑vis international obligations of member states. Yet disconnection clauses raise much concern as contributing to further fragmentation of international law and may possibly have a disadvantageous effect on compliance with and consistency of legal standards in Europe.